2012
DOI: 10.5539/ijbm.v7n18p69
|View full text |Cite
|
Sign up to set email alerts
|

Mergers and Acquisitions in Banking: Understanding the IT Integration Perspective

Abstract: The aim of this exploratory study is to understand the key issues associated with integrating Information Technology (IT) in banking mergers and acquisitions (M&A). The study is undertaken by reviewing a number of high-profile cases and interviewing the IT practitioners who managed the corresponding processes. The result is a comprehensive review of a poorly understood and researched area providing insights into the significance of the IT-related elements in the M&A integration and specifics of the M&A IT inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
5
2
Order By: Relevance
“…To achieve that, a number of large-scale high-profile banking M&A cases were investigated by interviewing key senior level technology officers directly involved in the delivery of those projects. Some of the results of the study were published in another work, Kovela and Skok (2012), which among other things confirmed that IT is a critical resource and enabler in the business model of modern banking and therefore a clear link between the business strategy driving the merger and the priority of the IT integration tasks which are key for the efficiency of M&A transactions. The current paper builds on and complements these findings by proposing a framework for those embarking on the process.…”
Section: Aims and Objectivessupporting
confidence: 48%
See 1 more Smart Citation
“…To achieve that, a number of large-scale high-profile banking M&A cases were investigated by interviewing key senior level technology officers directly involved in the delivery of those projects. Some of the results of the study were published in another work, Kovela and Skok (2012), which among other things confirmed that IT is a critical resource and enabler in the business model of modern banking and therefore a clear link between the business strategy driving the merger and the priority of the IT integration tasks which are key for the efficiency of M&A transactions. The current paper builds on and complements these findings by proposing a framework for those embarking on the process.…”
Section: Aims and Objectivessupporting
confidence: 48%
“…Firstly, M&As fail to increase shareholder value in more than half of the cases (58.3% between 1992 and 2006 according to Cools et al, 2007) and in banking specifically that can often be directly attributed to the IT integration related problems (Williams, 2005;Williams et al, 2007;Kovela & Skok, 2012;Deloitte, 2014;The Mergermarket Group, 2014), e.g. the cases of Santander's takeover of Alliance and Leicester (Williams, 2010) and integration of the RBS Group's IT infrastructure (King, 2012 andBoyce, 2012).…”
Section: Aims and Objectivesmentioning
confidence: 99%
“…Tanriverdi and Uysal (2015) give an account of many sources discussing the high complexity and cost of IT M&A integration which is relevant to an IT-heavy industry such as banking. Kovela and Skok (2012) and Roehl-anderson (2013) also indicate that despite the expense of post-merger IT integration often being considered immaterial in the overall scale of the deal the costs are still substantial. Learning to do the task properly would therefore potentially save organisations engaged in M&A funds which could be deployed more productively elsewhere.…”
Section: )mentioning
confidence: 99%
“…An earlier academic paper by one of the authors of the current study, Kovela and Skok (2012), proposed a summative layout of the M&A IT integration for banking institutions, updated and represented below in Figure 1.…”
Section: Manda and It Integration Process Timeline For Bankingmentioning
confidence: 99%
See 1 more Smart Citation